A simple mechanism to deal with sequential code in dataflow architectures - Cavenaghi, Marcos Antônio [UNESP]; Travieso, G.; Neto, A. G. (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 1998)
The aim of this work is to propose a simple and efficient mechanism to deal with the problem of executing sequential code in a pure dataflow machine. Our results is obtained with a simulator of Wolf [4] architecture. The implemented mechanism improved the architecture performance when executing sequential code and we expect that this improvement could be better if we use some heuristics to deal with some special groups of instructions such as branch operations. Further research will show us if this is true.